Adams and Victor's principles of neurology - Ropper, Allan H.; Klein, Joshua; Samuels, Martin A. (New York : McGraw-Hill Education, 2019)
The wise application of science, evidence from trials, and the traditional virtues of the neurological history and examination are the main purpose of this edition of Principles of Neurology--
PART 1: THE CLINICAL METHOD OF NEUROLOGY -- Chapter 1: Approach to the Patient With Neurologic Disease -- Chapter 2: Diagnostic Testing in Neurologic Disease -- PART 2: CARDINAL MANIFESTATIONS OF NEUROLOGIC DISEASE -- Part 2: Cardinal Manifestations of Neurologic Disease: Introduction -- Section 1: Disorders of Motility -- Section 1: Disorders of Motility: Introduction -- Chapter 3: Paralysis and Weakness -- Chapter 4: Disorders of Movement and Posture -- Chapter 5: Ataxia and Disorders of Cerebellar Function -- Chapter 6: Disorders of Stance and Gait -- Section 2: Pain and Disorders of Somatic Sensation -- Section 2: Pain and Disorders of Somatic Sensation: Introduction -- Chapter 7: Pain -- Chapter 8: Disorders of Non-Painful Somatic Sensation -- Chapter 9: Headache and Other Craniofacial Pains -- Chapter 10: Pain in the Back, Neck, and Extremities -- Section 3: Disorders of the Special Senses -- Section 3: Disorders of the Special Senses: Introduction -- Chapter 11: Disorders of Smell and Taste -- Chapter 12: Disturbances of Vision -- Chapter 13: Disorders of Ocular Movement and Pupillary Function -- Chapter 14: Deafness, Dizziness, and Disorders of Equilibrium -- Section 4: Epilepsy and Disorders of Consciousness -- Chapter 15: Epilepsy and Other Seizure Disorders -- Chapter 16: Coma and Related Disorders of Consciousness -- Chapter 17: Faintness and Syncope -- Chapter 18: Sleep and Its Abnormalities -- Section 5: Derangements of Intellect, Behavior, and Language Caused by Diffuse and Focal Cerebral Disease -- Section 5: Derangements of Intellect, Behavior, and Language Caused by Diffuse and Focal Cerebral Disease: Introduction -- Chapter 19: Delirium and Other Acute Confusional States -- Chapter 20: Dementia, the Amnesic Syndrome, and the Neurology of Intelligence and Memory -- Chapter 21: Neurologic Disorders Caused by Lesions in Specific Parts of the Cerebrum -- Chapter 22: Disorders of Speech and Language -- Section 6: Disorders of Energy, Mood, and Autonomic and Endocrine Functions -- Chapter 23: Fatigue, Asthenia, Anxiety, and Depression -- Chapter 24: The Limbic Lobes and the Neurology of Emotion -- Chapter 25: Disorders of the Autonomic Nervous System, Respiration, and Swallowing -- Chapter 26: The Hypothalamus and Neuroendocrine Disorders -- PART 3: GROWTH AND DEVELOPMENT OF THE NERVOUS SYSTEM AND THE NEUROLOGY OF AGING -- Chapter 27: Normal Development and Deviations in Development of the Nervous System -- Chapter 28: The Neurology of Aging -- PART 4: MAJOR CATEGORIES OF NEUROLOGIC DISEASE -- Chapter 29: Disturbances of Cerebrospinal Fluid, Including Hydrocephalus, Pseudotumor Cerebri, and Low-Pressure Syndromes -- Chapter 30: Intracranial Neoplasms and Paraneoplastic Disorders -- Chapter 31: Bacterial, Fungal, Spirochetal, and Parasitic Infections of the Nervous System -- Chapter 32: Viral Infections of the Nervous System and Prion Diseases -- Chapter 33: Stroke and Cerebrovascular Diseases -- Chapter 34: Craniocerebral Trauma -- Chapter 35: Multiple Sclerosis and Other Inflammatory Demyelinating Diseases -- Chapter 36: Inherited Metabolic Diseases of the Nervous System -- Chapter 37: Developmental Diseases of the Nervous System -- Chapter 38: Degenerative Diseases of the Nervous System -- Chapter 39: The Acquired Metabolic Disorders of the Nervous System -- Chapter 40: Diseases of the Nervous System Caused by Nutritional Deficiency -- Chapter 41: Disorders of the Nervous System Caused by Alcohol, Drugs, Toxins, and Chemical Agents -- PART 5: DISEASES OF SPINAL CORD, PERIPHERAL NERVE, AND MUSCLE -- Chapter 42: Diseases of the Spinal Cord -- Chapter 43: Diseases of the Peripheral Nerves -- Chapter 44: Diseases of the Cranial Nerves -- Chapter 45: Diseases of Muscle -- Chapter 46: Disorders of the Neuromuscular Junction, Myotonias, and Persistent Muscle Fiber Activity -- PART 6: PSYCHIATRIC DISORDERS -- Chapter 47: Anxiety Disorders, Hysteria, and Personality Disorders -- Chapter 48: Depression and Bipolar Disease -- Chapter 49: Schizophrenia, Delusional, and Paranoid States.
Includes bibliographical references and index.
Keywords: Nervous System Diseases; Neurologic Manifestations